Non-typhoidal Salmonella bacteraemia in paediatric leukaemia patients - Yaman, Yöntem; Devrim, İlker; Ozek, Gulcihan; Demirağ, Bengü; Oymak, Yeşim; Gülfidan, Gamze; Vergin, Canan (Contemporary Oncology/Współczesna Onkologia, 2018)
Non-typhoidal Salmonella (NTS) is an important pathogen that causes gastroenteritis, bacteraemia, and focal infections. Herein, we present our experience with bloodstream infections caused by Salmonella in paediatric leukaemia patients, which has been reported for the first time in both Europe and the US. According to our research, NTS might be a cause of serious infections in paediatric haematology-oncology patients. Following a low bacterial diet and increasing the hygiene of both the children and their surroundings would be beneficial in preventing these infections.